2016
DOI: 10.1183/13993003.01867-2016
|View full text |Cite
|
Sign up to set email alerts
|

Adding complexity to plexogenic arteriopathy

Abstract: @ERSpublicationsIn PAH, a wide range of abnormal pulmonary vascular manifestations exist, all arising from the endothelium http://ow.ly/IWH2305bXpQIn a landmark paper in the field of pulmonary hypertension research, Donald Heath and Jesse Edwards, in 1958, described the pulmonary vascular pathology that accompanies severe forms of pulmonary hypertension [1]. Examining lung tissue samples from patients with pulmonary hypertension associated with congenital heart disease and patients with primary pulmonary hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In an intriguing recent report, Abman's group (29) has suggested that the plexiform lesions may not even arise in the pulmonary circulation at all but in the bronchial circulation, as a result of the opening of intrapulmonary bronchial anastomoses in response to increased pulmonary arterial pressures overloading the bronchial venous bed. This concept is further supported by a report that patients harboring BMPR2 mutations exhibit more marked bronchial arterial remodeling and angiogenesis and are more prone to hemoptysis than patients without these mutations (118). Patients with BMPR2 mutations are known to exhibit a more severe PAH phenotype, present earlier, and have a worse prognosis than those with idiopathic disease (27), consistent with a possible relationship between severity of hemodynamic abnormalities and remodeling within the bronchial venous bed.…”
Section: Ph Is a Disease Of Ec Apoptosis Not Proliferation By Duncanmentioning
confidence: 67%
“…In an intriguing recent report, Abman's group (29) has suggested that the plexiform lesions may not even arise in the pulmonary circulation at all but in the bronchial circulation, as a result of the opening of intrapulmonary bronchial anastomoses in response to increased pulmonary arterial pressures overloading the bronchial venous bed. This concept is further supported by a report that patients harboring BMPR2 mutations exhibit more marked bronchial arterial remodeling and angiogenesis and are more prone to hemoptysis than patients without these mutations (118). Patients with BMPR2 mutations are known to exhibit a more severe PAH phenotype, present earlier, and have a worse prognosis than those with idiopathic disease (27), consistent with a possible relationship between severity of hemodynamic abnormalities and remodeling within the bronchial venous bed.…”
Section: Ph Is a Disease Of Ec Apoptosis Not Proliferation By Duncanmentioning
confidence: 67%
“…These complex vascular formations originate from the remodeled pulmonary arterial lumen and small precapillary arteries and contain endothelial as well as smooth muscle cells that express many angiogenic factors [7,48]. Furthermore, the molecular signals responsible for angiogenesis within the plexiform lesions have been thought to be a continuous process involving the formation of new blood vessels from pre-existing blood vessels driven by their dysregulated molecular make-up (e.g., altered VEGF signaling) called "misguided angiogenesis," a term given by Tuder and Voelkel [13,15,[49][50][51][52] owever, the development and overall significance of the plexiform lesion are not yet fully understood. It has been generally thought that the angiogenic processes that coordinate the vascular remodeling and dysfunction in PAH are solely determined by genetic cues, but many recent reports have shown that dysregulated metabolism may be involved [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of PAH may include symptoms such as dyspnea, fatigue, chest discomfort, cyanosis, and lower extremity swelling. At the histological level, severe PAH is marked by the presence of the so-called plexiform lesions, occlusive, glomeruloid-like vascular structures typically occurring distal to branch points of small pulmonary arteries [3,4]. These structures have been identified in individuals across various age groups [3,5], and the earliest occurrence of the lesions has been documented during in utero stages, exemplified by a case involving a 31-week stillborn fetus with premature closure of the ductus arteriosus and lung hypoplasia [6].…”
Section: Introductionmentioning
confidence: 99%